Changes in balance ability, power output, and stretch-shortening cycle utilisation after two high-intensity intermittent training protocols in endurance runners - Felipe García-Pinillos; Juan A. Párraga-Montilla; Víctor M. Soto-Hermoso; Pedro A. Latorre-Román (Elsevier, 2016)
Purpose: This study aimed to describe the acute effects of 2 different high-intensity intermittent trainings (HIITs) on postural control, countermovement jump (CMJ), squat jump (SJ), and stretch-shortening cycle (SSC) utilisation, and to compare the changes induced by both protocols in those variables in endurance runners. Methods: Eighteen recreationally trained endurance runners participated in this study and were tested on 2 occasions: 10 runs of 400 m with 90 s recovery between running bouts (10 × 400 m), and 40 runs of 100 m with 30 s recovery between runs (40 × 100 m). Heart rate was monitored during both HIITs; blood lactate accumulation and rate of perceived exertion were recorded after both protocols. Vertical jump ability (CMJ and SJ) and SSC together with postural control were also controlled during both HIITs. Results: Repeated measures analysis revealed a significant improvement in CMJ and SJ during 10 × 400 m (p < 0.05), whilst no significant changes were observed during 40 × 100 m. Indexes related to SSC did not experience significant changes during any of the protocols. As for postural control, no significant changes were observed in the 40 × 100 m protocol, whilst significant impairments were observed during the 10 × 400 m protocol (p < 0.05). Conclusion: A protocol with a higher number of shorter runs (40 × 100 m) induced different changes in those neuromuscular parameters than those with fewer and longer runs (10 × 400 m). Whereas the 40 × 100 m protocol did not cause any significant changes in vertical jump ability, postural control or SSC utilisation, the 10 × 400 m protocol impaired postural control and caused improvements in vertical jumping tests. Keywords: Long-distance runner, Postural control, Reactive strength, Training prescription, Vertical jump